1997
DOI: 10.1002/hep.510250126
|View full text |Cite
|
Sign up to set email alerts
|

4–Hydroxynonenal Levels Are Enhanced in Fetal Liver Mitochondria By In Utero Ethanol Exposure

Abstract: Studies in many laboratories show that ethanol can induce Lipid peroxidation has been implicated in ethanol-inoxidative stress in adult tissues and that this may be associduced liver injury and observed in fetal liver and brain ated with subsequent ethanol-related damage. 3,4 Likewise, after maternal ethanol consumption with mitochondria lipid peroxidation resulting from oxidative stress has been being the target organelles. This process generates a shown to increase in tissues/cells after in vivo and in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Fetal alcohol exposure has been shown to lead to an increase in lipid peroxidation in the brain and liver (Chen et al, 1997). There have been several studies documenting the use of antioxidants or ROS-clearing enzymes to decrease the rates of alcohol-induced malformations (Chen et al, 2004; Shirpoor et al, 2009; Patten et al, 2013; Parnell et al, 2010).…”
Section: Intersection Of Upr Apoptosis and Oxidative Stress In Dmentioning
confidence: 99%
“…Fetal alcohol exposure has been shown to lead to an increase in lipid peroxidation in the brain and liver (Chen et al, 1997). There have been several studies documenting the use of antioxidants or ROS-clearing enzymes to decrease the rates of alcohol-induced malformations (Chen et al, 2004; Shirpoor et al, 2009; Patten et al, 2013; Parnell et al, 2010).…”
Section: Intersection Of Upr Apoptosis and Oxidative Stress In Dmentioning
confidence: 99%
“…The levels of reactive lipid aldehydes are elevated in various oxidative stress-mediated diseases, including steatohepatitis [14], atherosclerosis [15], Alzheimer’s [16], cataract [17], diabetes [18] and cancer [19]. In fact, accumulation of reactive aldehydes is associated with the pathogenesis of these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is direct evidence that DAE leads to increased oxidative stress in several models. Ethanol exposure increases the production of reactive oxygen species (ROS) in fetal liver tissue ( Chen et al 1997 ) and brains ( Heaton et al 2002 ). Ramachandran et al (2003) observed increased apoptosis in cultured rat neurons after ethanol exposure in combination with significant increases in ROS.…”
mentioning
confidence: 99%